Cultivar x environment interaction on green ear yield in corn inoculated with Azospirillum brasilense, at low latitude - Dias, Vanderlan Carneiro; Peluzio, Joênes Mucci; Lima, Maria Dilma de; Benko, Guilherme; Lima Naoe, Alessandra Maria de; Reina, Evandro; Santos, Weder Ferreira dos; Santos, Layanni Ferreira Sodré; Afférri, Flávio Sérgio; Carneiro, Wânia Maria Dias (International Journal of Advanced Engineering Research and Science, 2021)
The cultivation of green corn has been increasingly important for small farmers, due to its economic and social importance, derived from consumption in natura in the form of green ears. Thus, the present work was carried out to study the behavior of corn cultivars, in the presence and absence of the bacterium Azospirillum brasilense, under different nitrogen doses, aiming at the productivity of green ears in cultivation under low latitude. Two trials were installed, one in the agricultural year 2019/20 and the other in the agricultural year 2020/21, in the central region of the State of Tocantins. The experimental design used in each assay was randomized blocks, with three replications. The treatments were arranged in subdivided plots, where treatments involving seed inoculation with the bacterium were allocated in the plots Azospirillum (C Az) and without inoculation of seeds (S Az), in the subplots five doses of nitrogen (00, 30, 60, 90 and 120 kg ha-1 N) and in the subplots eight maize cultivars. For each process (C Az and S Az), an adaptability and stability study were carried out using the Eberhart & Russell (1966) and environmental stratification by the method of Lin (1982), where the combination of each dose of N, in each assay and in each process (C Az e S Az) represented a distinct environment. There was a differential response of the cultivars between the processes with and without seed inoculation. Seed inoculation resulted in a higher increase in the productivity of green ears. Or BRS-3046 and AG-1051 adapted to the environments.